A Systematic Review: Halal Tourism Development in Indonesia - Samudra, Dio; Safagutan, Fahri; Silvi, Nok; Lutfiana, Eka; Aura, Hatma; Parniati (Iqtishodiah: Jurnal Ekonomi dan Perbankan Syariah, 2024)
This study analyses the potential and challenges in the development of halal tourism in Indonesia, which is becoming one of the fastest growing tourism destinations due to the increasing global Muslim population and halal lifestyle awareness. As a country with the largest Muslim population, Indonesia has various potentials in terms of culture, nature, and strong Islamic history. The government has been supporting this sector through policies and regulations, such as the Halal Product Guarantee Law, as well as the development of flagship halal tourism destinations. However, several challenges remain, including standardisation of halal services, coordination among stakeholders, and competition from other countries such as Malaysia and the United Arab Emirates. Utilisation of digital technology and strengthening human resources are also important factors in Indonesia's efforts to strengthen its position as a global halal tourism destination. This research emphasises the need to apply sustainability principles in the development of halal tourism to maintain long-term benefits for local communities and the environment.